Influence of dietary polyunsaturated fatty acids on glucose sensitivity, insulin resistance and cognitive function in a rat model - Tan, Ai Li (2014)
Insulin resistance (IR) occurs when there is an impaired response to insulin-dependent glucose regulation in the body. Hallmarks for insulin resistance include persistent hyperinsulinaemia and hyperglycaemia. In this present study, we are able to understand how insulin resistance occur in the molecular pathway because most studies are focusing on factors that cause insulin resistance such as diet and exercise rather than more in depth work. The objectives of this study were to investigate the changes in insulin sensitivity, body fat accretion and circulating leptin level in the body due to different ratio of n-6 and n-3 polyunsaturated fatty acids (PUFAs) supplementation. The histological changes in the liver will also be determined. The roles and expression levels of the relevant genes involved in fat metabolism such as peroxisome proliferator-activated receptor, (PPAR), selected adipokines and glucose transporters were examined in the rat model. At the end of the study, the rats were also examined to determine if there is any plausible link between cognitive ability, insulin resistance and dietary fatty acid supplementation in the test subjects. Male Sprague Dawley rats were used in this feeding trial which lasted more than 24 weeks. The animals were fed either a diet fortified with additional 10 % of fat made up primarily of either n-3 PUFA from Menhaden oil (MCD), n-6 PUFA from soybean oil (SCD), saturated butter fat (BCD) or an unsupplemented base diet (CD). Plasma insulin, glucose and the relevant adipokine levels were monitored at week 0, 10 and 22 of the experiment to determine the onset of insulin resistance. Liver histology examination was performed to determine the possible pathologies associated with long-term fat supplementation. Muscle and liver tissue samples were also sampled to determine the level of PPAR, tumor necrosis factor (TNF)- , glucose transporter (GLUT) 1 and GLUT4 gene expressions. The expression of the glucose transporter and selected biomarkers of insulin resistance was evaluated by real-time reverse transcription polymerase chain reaction method. The study was capped with cognitive ability evaluation of the rats using the Morris Water Maze. Results indicated that high n-3 PUFA supplementation in MCD rats delayed the onset of IR. MCD rats also had lower fat mass and fat percentage in the body, and moderate levels of leptin compared to other groups. This was due to the positive correlation between fat mass and leptin secretion. In BCD rats, they exhibited insulin resistance characteristic with high glucose and insulin level. This was due to the high saturated fat accumulation in their body. Other than that, PPARα and PPARγ genes were lowly expressed, as well as negligible levels of GLUT4 and GLUT1 readings in the liver and muscle cells. However, TNF-α gene expression were significantly higher in the insulin resistant BCD group, but much lower among the MCD and SCD groups. In addition the, the liver section of the BCD group showed lipid vacuolation in and between the hepatocytes. This will lead to the pathogenesis of liver pathology. The profound effects of dietary fatty acids on the functions of the central nervous system during cognition, memory and learning ability was evident in this study. Animals that were supplemented with saturated fats which were insulin resistant at this stage fared poorly in the Morris Water Maze Test. Contrastingly, non-insulin resistant animals from the MCD group fed with n-3 PUFA and normal animals from the CD group performed significantly better. In conclusion, this study demonstrated that high n-3 PUFA dietary fats delayed the onset of insulin resistance and reduces body fat accretion. Furthermore, it also highlights the high expression of PPARα,PPARγ, GLUT1 and GLUT4 genes while reducing the pro-inflammatory gene (TNF-α). High n-3 PUFA also exerts protective effect in the brain to enhance spatial learning and cognitive performance.